i hav my solution , but don't know if its correct,, Solve for x; x-3-2(6-2x) = 2(2x-5)
x-3-2(6-2x) = 2(2x-5)
x-3-2(6-2x) = 4x-10
x(6-2x)-4x = -10+5
6x-2x-4x = -5
-1 ( -x = -5 ) -1
x = 5
don't know if its correct....
i hav my solution , but don't know if its correct,, Solve for x; x-3-2(6-2x) = 2(2x-5)
x-3-2(6-2x) = 2(2x-5)
x-3-2(6-2x) = 4x-10
x(6-2x)-4x = -10+5 this step is wrong
6x-2x-4x = -5
-1 ( -x = -5 ) -1
x = 5
don't know if its correct....
Go back to the step highlighted above. As a general rule of thumb, it's usually easiest to expand ALL brackets first.